Synthesis of 2-Acylbenzothiazoles via the Cu(OTf)2-Catalyzed Tandem Reaction of β,β-Dihalidestyrenes with 2,2′-Disulfanediyldianilines - Zhou, Zeng-Le; Fang, Tao; Tang, Ri-Yuan; Zhang, Xing-Guo; Deng, Chen-Liang (Synlett, 2014)
A new method has been developed for the one-pot construction of 2-acylbenzothiazoles via the Cu(OTf)2-catalyzed tandem reaction of β,β-dihalidestyrenes with 2,2′-disulfane-diyldianilines. A variety of different dihalidestyrenes and diphenyldisulfanes were efficiently converted into the corresponding 2-acylbenzothiszole derivatives in the presence of Cu(OTf)2. Most importantly, this protocol allowed for the long chain 1,1-dibromohept-1-ene to be converted into the corresponding 2-hexylbenzo[d]thiazole in moderate yield.
Keywords: Cu(OTf)2; dihalidestyrene; diphenyldisulfane; 2-acylbenzothiazole; tandem reaction